(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
In the article we carry out a systematic review of the literature on university spin-offs. For both theoretical and practical reasons, the subject of this type of company has grown strongly in recent years. After presenting the main descriptive indicators, we analyze the review from the perspective of organizational performance. We use Jeffrey Pfeffer’s approach by classifying the literature on university spin-offs through structural contingency, organizational ecology, human resources, and networks. This approach has allowed us to characterize four useful analytical dimensions for future studies on university spin-offs.